Misconception of High School Students on Acid-Base Topics and Effectiveness of Argument-Driven Inquiry Learning Model as an Effort to Improve Misconception - Anjamputra A. Embisa; Subandi Subandi; Fauziatul Fajaroh (Jurnal Pendidikan Sains, 2019)
Abstract: The objectives of this study were: 1) calculate the average percent of students in each sub-topic on the pretest, posttest, and delay test, 2) identify students’ misconceptions in acid-base topic, 3) test the effectiveness of the ADI learning model in correcting students’ misconceptions in acid-base topic, and 4) measuring retention of students conceptual understanding of acid-base topic after being given improvements by the ADI learning model. The misconceptions found were used as a basis for reference in implementing the ADI learning model. The results showed that most students did not understand the concept (55%) while the misconceptions (24%) and understood the concept (21%). After improvement using the ADI learning model, the number of students who understood the concept increased to 64%, misconceptions of students’ decreased to 17%, students who did not understand the concept also declined to 19%. This shows that most students successfully construct their understanding.Key Words: CRI technique, ADI learning model, misconception, acid-base topicAbstrak: Penelitian ini dilakukan dengan tujuan (1) menghitung rerata siswa disetiap sub-sub topik pada pretes, postes, dan tes tunda, (2) mengidentifikasi kesalahan konsep siswa pada materi asam-basa, (3) menguji keefektifan model pembelajaran ADI (Argument-Driven Inquiry) dalam memperbaiki kesalahan konsep siswa pada materi asam basa, dan 4) Mengukur retensi pemahaman konsep siswa pada materi asam basa setelah diberikan perbaikan dengan model pembelajaran ADI. Kesalahan konsep yang ditemukan digunakan sebagai dasar acuan dalam pelaksanaan model pembelajaran ADI. Hasil penelitian menunjukkan bahwa, sebagian besar siswa ternyata tidak paham konsep (55%) sementara yang miskonsepsi sebanyak 24% dan paham konsep sebesar 21%. Setelah dilakukan perbaikan dengan model pembelajaran ADI, jumlah siswa yang paham konsep meningkat menjadi 64%, siswa dengan miskonsepsi menurun menjadi 17%, siswa dengan ketidakpahaman konsep juga menurun menjadi 19%. Hal ini menunjukkan sebagian besar siswa berhasil mengkonstruk pemahamannya.  Kata kunci: teknik CRI, model pembelajaran ADI, miskonsepsi, materi asam-basa